MADZHAB DALAM SYARIâAT ISLAM - M Saleh, M Saleh (ISTINBATH JURNAL HUKUM, 2004)
The majority of Islamic community in this world had hold on the fatwa (advice on relegious matters) of their Ulama Madzhab on their relegious matters. But also they profess to others i.e, Dzahiri and Syiâite sects. Beside that there was also some scholars of relegion who took apartÂ  from that Madzhab at all, they didnâtÂ  follow any other advice on their relegious matters teachers, but they hold on they selfes opinion. Of course, it caused to uncertainty mind or confusedÂ  to Islamic Community, who had along time ago hold on to the fatwa of their Scholar opinion. So, it is better to the writer to study how was the madzhab stand on relegious affair.Key Words : advice on relegious matters, profess to, scholars of relegion, took apartÂ  from, stand on